Analisis Korelasi Pengetahuan Gizi, Asupan Lemak Camilan, dan Pola Konsumsi Camilan dengan Status Gizi Remaja di Surabaya - Fikriyah Al'aliyyu; Annis Catur Adi (Universitas Airlangga, 2023)
Background: Adolescents are a group that is vulnerable to nutritional problems because this period includes a period of growth and development with physical, psychological and cognitive changes. There are several factors that affect nutritional status, such as the level of knowledge about nutrition and food consumption Objectives: Analyzing the correlation between the level of nutritional knowledge, snack fat intake and snack consumption patterns with the nutritional status of adolescents in Surabaya Methods: This research is a type of correlational research with a cross sectional study. The number of samples was 64 adolescents selected by proportional random sampling. Each variable studied was tested with the Spearman test. Adolescents' nutritional status were recorded with anthropometric measurements, nutritional knowledge with a questionnaire and snack consumption with the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) Results: there was a significant correlation between nutritional knowledge with nutritional status (p=0.042) and no significant correlation between nutritional status with snack fat intake (p=0.152) and snack consumption pattern (p=0.945) Conclusions: The higher level of nutritional knowledge possessed by adolescents, the more likely they will have good nutritional status.